O desenvolvimento de (2-m)³ e:
Soluções para a tarefa
Respondido por
7
= (2 - m)³
= (2 - m)².(2 - m)
= (4 - 2.2m + m²).( 2 - m)
= (4 - 4m + m²).(2 - m)
= 8 - 4m - 8m + 4m² + 2m² - m³
= 8 - 12m + 6m² - m³
= - m³ + 6m² - 12m + 8
= (2 - m)².(2 - m)
= (4 - 2.2m + m²).( 2 - m)
= (4 - 4m + m²).(2 - m)
= 8 - 4m - 8m + 4m² + 2m² - m³
= 8 - 12m + 6m² - m³
= - m³ + 6m² - 12m + 8
ElenRegina:
Vlw!!!!!!
Perguntas interessantes
Matemática,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Geografia,
1 ano atrás